Chemically stabilized reduced graphene oxide/zirconia nanocomposite: synthesis and characterization. (28th November 2017) - Sagadevan, Suresh; Zaman Chowdhury, Zaira; Hoque, Md Enamul; Podder, Jiban
Abstract: In this research, chemical method was used to fabricate reduced graphene oxide/zirconia (rGO/ZrO2 ) nanocomposite. X-ray Diffraction analysis (XRD) was carried out to examine the crystalline structure of the nanocomposites. The nanocomposite prepared here has average crystallite size of 14 nm. The surface morphology was observed using scanning electron microscopic analysis (SEM) coupled with electron dispersion spectroscopy (EDS) to detect the chemical element over the surface of the nanocomposites. High-resolution Transmission electron microscopic analysis (HR-TEM) was carried out to determine the particle size and shape of the nanocomposites. The optical property of the prepared samples was determined using UV–visible absorption spectrum. The functional groups were identified using FTIR and Raman spectroscopic analysis. Efficient, cost effective and properly optimized synthesis process of rGO/ZrO2 nanocomposite can ensure the presence of infiltrating graphene network inside the ZrO2 matrix to enhance the electrical properties of the hybrid composites up to a greater scale. Thus the dielectric constant, dielectric loss and AC conductivity of the prepared sample was measured at various frequencies and temperatures. The analytical results obtained here confirmed the homogeneous dispersion of ZrO2 nanostructures over the surface of reduced graphene oxide nanosheets. Overall, the research demonstrated that the rGO/ZrO2 nano-hybrid structure fabricated here can be considered as a promising candidate for applications in nanoelectronics and optoelectronics.